A decade of open access policy at the Gates Foundation based on experimentation, evidence and evolution - Ashley Farley (Insights: The UKSG Journal)
This article provides an in-depth look at the Gates Foundation’s open access (OA) policy journey as 2025 marks a decade of OA policy for the foundation. There have been two iterations of the policy – the original version that was launched in 2015 with a focus on gold OA, and which was then adapted in 2021 to reflect the Plan S principles, including limitations for publisher payments based on journal type and repository deposits. Now, in response to the ever-evolving needs of the scholarly ecosystem, the foundation is updating its policy again to strive for broader impact and to support practices that drive greater inclusion of scientists around the world, particularly those from low- and middle-income countries. This article will provide a deep dive into the decisions and data used to define a more equitable approach to dissemination of the research funded by the foundation.